New literacies and the English curriculum : multimodal perspectives - Unsworth, Len (Continuum, 2008)
In an age where the use of electronic media is expanding and replacing traditional text-based learning, literacies are becoming important in the school classroom. This volume examines how literacies can be used in the English curriculum, and presents a series of research-based studies applied to various levels of school-age education